Gross Morphology and Morphometrical Studies on the Vertebral Column of Indian Giant Flying Squirrel (Petaurista philippensis) - Thippan, Mayakkannan; Lakshmishree, K. T.; Melinamani, Dhoolappa; Manjunath, S. S.; Jayaramu, G. M.; Vinay, S. (International Journal of Livestock Research, 2019)
The present study was conducted on the gross anatomical features of the vertebral column of Indian giant flying squirrel (Petaurista philippensis). It belongs to the order rodentia and Sciuridae family. The bones of vertebral column were collected during the post-mortem examination at Veterinary College, Shivamogga, Karnataka. The vertebral formula was found to be C7, T12, L7, S3 and Cy27. The foramen transversarium was noticed in all the cervical vertebrae except in C7. The width and length of the centrum progressively increased from L1 to L7. Haemal arch and haemal processes were observed in Cy4 to Cy9 and Cy10 to Cy19 respectively. The variations in neural spine, vertebral body length and transverse process were observed in all the vertebrae. So, these variations in the vertebral column may be attributed to the specialized movements such as gliding, lifting and balancing the body of Indian giant flying squirrel.